Positron emission tomography imaging of novel AAV capsids maps rapid brain accumulation - Jai Woong Seo (Nature Portfolio, 2020)
Adeno-associated viruses (AAVs) can be targeted in a tissue-specific manner, but their tissue accumulation cannot be assessed in a non-invasive manner. Here the authors conjugate a multivalent chelator labelled with Cu-64 to the surface of AAVs and image the brain accumulation of the PHB.eB capsid by PET.